School-Based Nutrition Education as a Community Engagement Program to Enhance Adolescents’ Awareness of Sugar, Salt, and Fat Intake in Banyuwangi - Muhammad Ridwan; Jhonatan Rameldo Hutasoit; Muhammad Hisyam; Faradiva Husna Azizah; Septa Indra Puspikawati (Alesha Media Digital, 2026)
Excessive consumption of sugar, salt, and fat among adolescents remains a public health particularly related to low nutritional literacy and limited understanding among students regarding safe limits for sugar, salt, and fat (SSF) consumption. The Youth Red Cross (PMR) as part of the school community has strategic potential as a partner and promoter of peer health, but still needs capacity building in nutrition education. To address this issue, school-based nutrition education activities are implemented as a community engagement program with the aim of increasing students' knowledge, awareness, and involvement in promoting healthier consumption of SSF. The activity involved 150 Youth Red Cross (PMR) students from five senior and vocational high schools in Banyuwangi Regency. Teachers and PMR members were actively engaged as community partners in planning, facilitating, and supporting the implementation of the program. Educational activities were delivered through interactive discussions, the use of familiar food examples, reflective group sessions, and basic health screening to connect nutrition messages with students’ real-life conditions. Program outcomes were documented as part of routine activity evaluation using a 10-item questionnaire administered before and after the sessions. An increase in average scores was observed, indicating improved short-term understanding; however, the primary contribution of the program lies in enhanced student engagement, peer interaction, and awareness of healthier dietary choices. The activity also encouraged reflection and dialogue within the school environment, suggesting positive social impact beyond individual knowledge gains. Overall, this community-based initiative demonstrates a feasible and empowering model for integrating nutrition education into routine school health activities.